Rapid effect of eye movement desensitization and reprocessing (EMDR) in treatment of psychogenic vomiting: Case report - (:unkn) unknown (KLINIK PSIKIYATRI DERGISI, 2020)
Psychogenic vomiting is an uncommon medical condition that usually occurs with severe and recurrent vomiting without an underlying organic cause. Although various pharmacological and therapeutic methods have been tried in the treatment of this condition, there is no clear treatment method. Eye Movement Desensitization and Reprocessing (EMDR) can be considered a good treatment alternative if there is a traumatic event in the underlying formation of psychogenic vomiting. To the best of our knowledge, there are no cases of efficacy of EMDR in psychogenic vomiting in the literature. The aim of the present case was to investigate the clinical usefulness of EMDR due to the presence of traumatic memories which may be associated with the symptom of psychogenic vomiting. As a result; as seen in our case, it should be considered that EMDR may be a treatment alternative in cases with psychogenic vomiting of traumatic origin.
Keywords: Psychogenic vomiting; EMDR; psychotherapy; NAUSEA; HYPNOSIS; THERAPY